Challenges to Tackling Antimicrobial Resistance Economic and Policy Responses - Anderson, Michael; Cecchini, Michele; Mossialos, Elias (Social Sciences, 2020)
An accessible overview of the challenges in tackling AMR, and the economic and policy responses of the 'One Health' approach. It will appeal to policy-makers seeking to strengthen national and local polices tackling AMR, as well as students and academics who want an overview of the latest scientific evidence regarding effective AMR policies.